2020
DOI: 10.1111/bph.15301
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic–pharmacodynamic model for the MET tyrosine kinase inhibitor, savolitinib, to explore target inhibition requirements for anti‐tumour activity

Abstract: Background and Purpose: Savolitinib (AZD6094, HMPL-504, volitinib) is an oral, potent, and highly MET receptor TK inhibitor. This series of studies aimed to develop a pharmacokinetic-pharmacodynamic (PK/PD) model to link inhibition of MET phosphorylation (pMET) by savolitinib with anti-tumour activity.Experimental Approach: Cell line-derived xenograft (CDX) experiments using human lung cancer (EBC-1) and gastric cancer (MKN-45) cells were conducted in athymic nude mice using a variety of doses and schedules of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 44 publications
(54 reference statements)
2
14
0
Order By: Relevance
“…around the need for prolonged, high levels of MET inhibition for clinical activity and identified once-and twicedaily dosing, respectively, as optimal (Jones et al, 2020;Xiong et al, 2021). In the present study, we confirm that persistent target inhibition results in a stronger, phenotypic viability effect as our washout effects on pMET and viability correlate well (Fig.…”
Section: Importance Of Sustained Effects To Induce the Desired Phenot...supporting
confidence: 82%
See 1 more Smart Citation
“…around the need for prolonged, high levels of MET inhibition for clinical activity and identified once-and twicedaily dosing, respectively, as optimal (Jones et al, 2020;Xiong et al, 2021). In the present study, we confirm that persistent target inhibition results in a stronger, phenotypic viability effect as our washout effects on pMET and viability correlate well (Fig.…”
Section: Importance Of Sustained Effects To Induce the Desired Phenot...supporting
confidence: 82%
“…In clinical settings, MET inhibitors can be differentiated by pharmacokinetic characteristics such as volume of distribution and half-life, which not only influence drug dosage (Jones et al, 2020;Xiong et al, 2021), but also potentially modulate primary pharmacology and the risk:benefit ratio of therapeutic agents. In particular, volume of distribution is largely driven by specific and unspecific binding of the therapeutic agent to intracellular proteins and membranes, and to a lesser extent by the stability of the drug-target complex and lysosomal retention on a subcellular level (Hamid and Krise, 2016;Schmitt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mouse population PK models for savolitinib and osimertinib previously developed were used as a starting point in these analyses ( 34, 35 ). A direct response maximum effect (E max ) model linking savolitinib plasma concentration to inhibition of pMET and TGI had been evaluated previously ( 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…Savolitinib has demonstrated antitumor effects in combination with gefitinib in a phase Ib study (NCT02511106) in patients with EGFRm, MET-amplified NSCLC, and in combination with osimertinib in the phase Ib TATTON study (NCT02143466) in patients with MET-amplified, EGFRm, advanced NSCLC, who had disease progression on a previous EGFR-TKI ( 11–13 ). A recent study of savolitinib in PDX and cell line–derived xenograft models suggests that high and durable levels of MET inhibition are needed for optimal monotherapy in preclinical models ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early on, in vitro studies have established inhibitory effect of savolitinib on growth of gastric cells lines, while in vivo studies observed anti-tumor activity in human xenograft tumor models of MET -amplified gastric cancer and PRCC [ 33 , 34 , 35 ]. Another study by Jones and colleagues related to pharmacokinetic-pharmacodynamic (PK-PD) model observed inhibition of phosphorylated-MET by savolitinib at an effective concentration (EC)50 of 0.35 ng/mL and EC90 of 3.2 ng/mL in a cell line-derived xenograft (CDX) mice model using human lung cancer (EBC-1) and gastric cancer (MKN-45) cells [ 36 ]. Furthermore, PK studies in healthy male Chinese volunteers administered with single oral savolitinib doses of 200, 400 and 600 mg following an overnight fast or a high-fat and high-calorie breakfast prior to dosing showed no clinically relevant impact on PK and bioavailability of savolitinib [ 37 ].…”
Section: Savolitinib In Briefmentioning
confidence: 99%